Analyzing campus built environment in determining sense of community of universities in Davao City - Lampasa, Jasper Andrei E. (2018)
A campus with a good sense of community means that students interact more with each other and also with other members of the university. Thus, the campus built environment has a significant influence on the well-being of users. The purpose of this study is to determine how the built environment of university campuses in Davao City affect their sense of community and propose a campus design that promotes a high sense of community within the university. In obtaining the needed data, survey questionnaires were handed out to undergraduate students for four universities in Davao City. The campuses were evaluated based on undergraduate students? assessment on public spaces inside the campus built environment and how it affected their perception on sense of community within the campus using the (state the survey name used). Aside from surveys, ocular visits and photo documentation were also conducted inside the four campuses to qualify the data obtained. Results show that campus facilities such as classrooms, student centers, and other spaces inside the campus affects its sense of community. The common physical factors and activities of these facilities were used in developing design guidelines for university campuses in order to enhance their sense of community. The said guidelines were applied in proposing the design of the College of Science and Mathematics Complex of the University of the Philippines Mindanao.